HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN PRESTASI AKADEMIK - Ahmad Fatonik; Yusi Susanti; Siti Roudhotul Jannah (CV. ADIBA AISHA AMIRA, 2025)
This study aims to explore the relationship between students' learning motivation and their academic achievement at SMAN 2 Banjit. A quantitative methodology was adopted, specifically a correlational design. Sampling was conducted using simple random sampling involving 60 students in grade XI. Data collection tools included a learning motivation measurement questionnaire and documentation of semester reports for the second semester of the 2023/2024 academic year. The findings revealed a strong positive correlation between learning motivation and academic achievement (r = 0.628, p <0.01). This indicates that as students' learning motivation increases, their academic success also increases.